Aerobic fitness of starter and non-starter soccer players in the Champion`s League - Paraskevas, G.; Hadjicharalambous, M. (Journal of Human Kinetics, 2018)
To identify individual response patterns in selected aerobic fitness variables of regular starters (ST; N = 7) and non-starters (Non-ST; N = 10), top level professional soccer players were tested for maximal oxygen uptake (VO2max), velocity at 4 mM of lactate (V4), velocity at maximal oxygen uptake (?VO2max) and oxygen pulse (O2-pulse) in July and December following consecutive periods of fixture congestion. V4 was the only variable that increased significantly in December compared to July (15.1 ± 0.5 vs. 14.6 ± 0.5, p = 0.001). There was an almost certain beneficial large mean team change for V4 (ES = 1.2 (0.67; 1.57), 100/0/0), while beneficial mean team changes were less likely for ?VO2max and O2-pulse [ES = 0.31 (-0.08; 0.70), 68/30/2 and ES = 0.24 (0.01; 0.49), 64/36/0, respectively] and unclear for VO2max (ES = 0.02 (-0.31; 0.70), 18/69/13). With the exception of V4 where 10 out of 17 players (7 ST and 3 Non-ST) showed positive changes higher than the biological variability, all other variables were characterized by a substantial proportion of changes lower than the biological variability. The present study demonstrated that aerobic fitness variables that require maximal effort may be characterized by greater variability of the individual response pattern compared to that of submaximal aerobic fitness variables irrespective of the accumulated game time. Submaximal aerobic fitness variables appear to be more informative in the physiological evaluation of top level soccer players and this may be an advantage during exposure to periods of consecutive games.